Existence and Uniqueness of Periodic Solutions for Some Nonlinear $ψ-$Hilfer Fractional Coupled Systems - Bouriah, Soufyane; Salim, Abdelkrim; Benchohra, Mouffak (Discontinuity, Nonlinearity, and Complexity, 2026)
The main goal of this paper is to study the existence and uniqueness of periodic solutions for some class of nonlinear fractional coupled systems with $ψ-$Hilfer derivative. The proofs are based upon the coincidence degree theory of Mawhin with several types of conditions. To show the efficiency of the stated result, illustrative examples will be given.